PENGABDIAN KEPADA MASYARAKAT SEMINAR NASIONAL ONLINE “KOMPETENSI, PELUANG, DAN TANTANGAN PEREKAM MEDIS & INFORMASI KESEHATAN DI ERA INDUSTRI 4.0 - Meliana; Garis Gemilang; Indah Kristina; Ima Rusdiana (MEDICORDHIF Jurnal Rekam Medis, 2022)
Community Service is one of the Tri Dharma of Higher Education, namely education, research, and community service. One of the realizations of community service carried out by APIKES BHJ is in the form of a national seminar with the theme "PMIK Competencies, Opportunities & Challenges in the Industrial Era 4.0". The activity is carried out online using the Zoom Meeting media. The background of this activity is to stay productive in the COVID-19 pandemic situation. Technological progress is developing very quickly. As a PMIK worker, you are required to be adaptive to follow developments, and even be able to improve your skills and knowledge so that later you become a PMIK that is superior and highly competitive. The flow of change in the era of the industrial revolution 4.0, demands that all health workers and health services provided must be adaptive and able to adapt to the latest technological developments. This activity will be held on Wednesday, March 17, 2021, at 08.30 WIB to 12.30 WIB. Followed by 431 participants consisting of 151 students, 161 PMIK, 119 general participants. Keywords ; PKM, PMIK, industry 4.,